Buckling of a twisted rod with centralizers in a tubing - Zhang, Qiang (2022)
A lot of research work has been done on the buckling of compressed rods with connectors in cylinders. However, very limited investigations on the buckling of a twisted sucker rod with centralizers in the progressing cavity pump well has been carried out so far. In our present study, a numerical computational strategy is proposed to investigate this highly important buckling problem. Firstly, a twisted sucker rod with or without centralizers is selected for finite element simulation and calculation, which verifies our solution method. Following that, the effects of centralizer number, centralizer spacing, sucker rod diameter and tubing diameter on the critical torque are analyzed. It is found that the clearance ratio, i.e., the ratio of the clearance between the centralizer and the tubing to the clearance between the sucker rod and the tubing, is the only factor that affects the dimensionless critical torque. With a centralizer, the critical rod length is usually reduced by 25% compared to the case of a rod with hinged restraint.